Lenalidomide potentially reduced the level of cell- associated HIV RNA and improved persistent inflammation in patients with HIV-associated cryptococcal meningitis a pilot study - Liu, Xiang; Zhu, Xueling; Peng, Xiaorong; Tao, Ran; Wan, Zhikai; Hui, Jiangjin; Guo, Yongzheng; Hang, Ying; Zhu, Biao (Frontiers in Cellular and Infection Microbiology, 2022)
Background. The HIV-1 reservoir is a major barrier to curative strategies. Inflammation is an important factor for HIV-1 reservoir persistence. Lenalidomide regulates inflammatory cytokines efficiently. We examined whether lenalidomide could inhibit HIV-1 transcription and reduce systemic inflammation in people living with HIV. Methods. Lenalidomide was administered orally for 48 weeks to patients with HIV-associated cryptococcal meningitis (HIV-CM). A HIV-1 latency model was treated with or without lenalidomide ex vivo for 5 days. The primary endpoints were change in HIV reservoir markers and inflammatory cytokines in both the cohort and cell model. Results. Thirteen participants were enrolled from May 2019 to September 2020. The median change in cell-associated (CA) HIV RNA between baseline and 48 weeks was 0.81 log10 copies/million peripheral blood mononuclear cells (PBMCs). The CA HIV RNA decreased significantly in the cohort (P = 0.021). Serum tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) gradually diminished with lenalidomide treatment until 48 weeks (P = 0.007, P = 0.014, respectively). C-reactive protein/IL-6/TNF-α and CA HIV RNA were significantly correlated (P = 0.0027, 0.0496, and 0.0346, respectively). Lenalidomide also significantly decreased HIV core P24 (P = 0.0038) and CA HIV RNA in CD8-depleted PBMCs (P = 0.0178) ex vivo. TNF-α and IL-6 were significantly reduced in the CD8-depleted PBMC supernatant (P = 0.004, P < 0.0001, respectively) while IL-10 levels increased significantly on lenalidomide compared to no-lenalidomide treatment (P < 0.0001). Conclusions. . Lenalidomide was preliminarily confirmed to reduce the level of cell- associated HIV RNA and improve persistent inflammation in patients with HIV-Associated cryptococcal meningitis, which was a potential intervention for clinical use to inhibit viral transcription of the HIV-1 reservoir and reduced HIV-related inflammation in HIV-1 patients during ART.